表达式5: equals "l" "i" "m" StartFraction, "f" left parenthesis, "x" plus "h" , right parenthesis minus "f" left parenthesis, "x" , right parenthesis Over "h" , EndFraction plus "l" "i" "m" StartFraction, "f" left parenthesis, "x" , right parenthesis minus "f" left parenthesis, "x" minus "h" , right parenthesis Over "h" , EndFraction “=”符号的前后不能为空白。=limfx+h−fxh+limfx−fx−hh
5
表达式6: equals 12 plus "l" "i" "m" StartFraction, "f" left parenthesis, "x" , right parenthesis minus "f" left parenthesis, "x" minus "h" , right parenthesis Over "h" , EndFraction “=”符号的前后不能为空白。=12+limfx−fx−hh
6
Substitute h for -h and we get (doesn’t change the limit as it exists from both sides since f’=12)
7
表达式8: equals 12 plus "l" "i" "m" StartFraction, "f" left parenthesis, "x" plus "h" , right parenthesis minus "f" left parenthesis, "x" , right parenthesis Over "h" , EndFraction “=”符号的前后不能为空白。=12+limfx+h−fxh